Raising Awareness of Export Potential as a Means of Empowering Human Resources and Strengthening Local Potential to Boost the Competitiveness of Kuap Village in the Global Market - Muthia Salsabila; Ratih Rosita; Devi Riani; Indra Arsandi; Andri Saputra; Wulan Septiani; Nurhayati Nurhayati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The village of Kuap in Pemayung Sub-district, Batanghari Regency, possesses a wide range of local potential, including the oil palm plantation sector, fisheries, areca nut production, and home-based micro-enterprises. However, this potential has not yet been fully utilised due to the community’s limited understanding of the basic concepts of export, product quality standards, and marketing opportunities in wider markets. This community service activity aims to enhance the awareness of the people of Kuap Village regarding the importance of human resource development and the strengthening of local potential as a first step towards accessing global markets. The activity was carried out using a qualitative descriptive observational approach, taking the form of an awareness-raising session featuring a guest speaker from Blantica Academy. The session utilised lectures, interactive discussions and a question-and-answer session, and was attended by around 20 participants comprising housewives, men, young people and local MSME operators. Observations revealed a high level of participation and enthusiasm among participants, reflected in the depth of the questions asked during the discussion sessions and the emergence of initial motivation to develop their businesses. The activity faced a number of challenges, including time constraints, varying levels of understanding among participants, and the lack of follow-up mentoring programmes; consequently, the sustainability of the programme’s impact still requires reinforcement through ongoing mentoring. It is hoped that this initiative will serve as a concrete first step towards strengthening the capacity of human resources and the competitiveness of Kuap Village’s local products in the global market.